Social Protection for Illegal Migrant Workers in Safety House and Trauma Center - Husmiati Husmiati; Nurdin Widodo; Alit Kurniasari; Ivo Noviana; M. Belanawane S (Jurnal Penelitian Kesejahteraan Sosial, 2017)
Thedone to asses the implementation of policies and social protection programs for the illegal migrant workers, the role and function of RPTC in conducting social protection for the illegal migrant workers, the role and function of RPTC in the process of reintegration of the illegal migrant worker in the area of origin, conditions of vulnerability experienced by illegal migrant workers during the mi gration process (transit, destination, place of origin) and the internal and external driving factors that cause the illegal migrant workers want to return to work abroad. This research use qualitative-desciptive approach, and implemented in Tanjung Pinang (Riau), DKI Jakarta, East Java and West Nusa Tenggara. The results showed the implementation of policies and social protection programs for the illegal migrant workers still regulation alone, role and function of RPTC in conducting social protection and reintegration processes the illegal migrant workers is as temporary shelters and as a rehabilitation center (temporary) the illegal migrant workers who experience mental illness and health problems.The illegal migrant workers also provided assistance productive economic so that they can get a source of income without having to leave the country and vulnerabilities experienced the illegal migrant workers varying from legal, social, economic, physical and psychological, as well as internal and external driving factors the illegal migrant workers want to return to work abroad.